2017
DOI: 10.1097/ogx.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Timing of Thromboembolic Events in Patients With Ovarian Cancer Undergoing Neoadjuvant Chemotherapy

Abstract: (Abstracted from Obstet Gynecol 2017;129(6):979–985) Thromboembolism in patients with ovarian and other cancers is associated with lower survival and poor quality of life. The estimated incidence of venous thromboembolism (VTE) among patients with ovarian cancer (OC) is 10% to 22%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Recently published smaller cohort studies propose that chemotherapy might have a higher influence on the risk of VTE than surgery. 11,12,23 The present study found similar HRs of VTE in EOC bleeding risk. 40,41 Gynecologic cancer patients are considered at high risk of developing VTE during chemotherapy according to the Khorana score and need only one other risk factor to fulfill the criteria to receive VTE prophylaxis during ambulant anticancer treatment according to the updated guidelines.…”
Section: Eoc Patients (%) Asupporting
confidence: 82%
See 2 more Smart Citations
“…Recently published smaller cohort studies propose that chemotherapy might have a higher influence on the risk of VTE than surgery. 11,12,23 The present study found similar HRs of VTE in EOC bleeding risk. 40,41 Gynecologic cancer patients are considered at high risk of developing VTE during chemotherapy according to the Khorana score and need only one other risk factor to fulfill the criteria to receive VTE prophylaxis during ambulant anticancer treatment according to the updated guidelines.…”
Section: Eoc Patients (%) Asupporting
confidence: 82%
“…9,10 Recent studies found that at least 10% of EOC patients developed VTE events during chemotherapy. 11,12 Treatment of EOC is complex and patients are often exposed to surgery and chemotherapy more than once, because relapse or progression is common. 13 The association between VTE and previously identified risk factors in EOC patients is complex, and has, to our knowledge, not previously been addressed with a multivariable time-dependent approach in a larger scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 3% of women with a new ovarian cancer diagnosis will have a concomitant VTE diagnosed before they start cancer treatment52; the risk of VTE approaches 12% during neoadjuvant chemotherapy55 and extends through at least the full course of primary therapy 56. The extended risk of VTE was also demonstrated in an analysis from the Million Women Study that showed the risk of VTE at 12 weeks post-operatively was 1/85 for cancer surgery and 1/365 for gynecologic surgery 57.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of VTE extends beyond the traditional 30 day post-operative complication window in these patients56 71 and is inherently present among those undergoing neoadjuvant chemotherapy for ovarian cancer 55. Extended low molecular weight heparin has been shown in two randomized, placebo controlled trials in solid tumors to reduce VTE during chemotherapy by 50% 85 86.…”
Section: Resultsmentioning
confidence: 99%